INFORMATION AND COMMUNICATION TECHNOLOGY AND DISTANCE LEARNING DELIVERY IN SELECTED NIGERIAN UNIVERSITIES (2014)
The Nigerian government adopted the distance learning approach to increase access to tertiary education. However, studies have been limited to implementation efforts with little focus on learning delivery modalities. This study, therefore, examined the delivery and performance of internet-mediated distance learning in selected Nigerian universities. Based on structuration theory, the study adopted survey research design. Three universities with established distance learning programme supported with ICT were selected; these were University of Ibadan (UI), University of Lagos (UNILAG) and National Open University of Nigeria (NOUN). Using multistage sampling procedures, a semi-structured questionnaire was administered to 179 (UI), 230 (UNILAG) and 461 (NOUN) proportionately selected students to obtain data on socio-economic characteristics (e.g. age, gender, occupation, marital status), knowledge and usage of internet and effect of virtual education on learning. Copies of another set of questionnaire were administered to 35 (UI), 72 (UNILAG) and 93 (NOUN) purposively selected tutors that identified the possible effects of internet-mediated learning. Eighteen FGD’s were conducted to the students based on their level of studies to identify challenges that may impede adoption of internet-mediated learning. Nine KII and IDI were conducted with policy makers and distance learning administrators respectively on viability of internet approach to learning. A non-participant structured observation method was further deployed to check the adequacy of facilities available in the three universities. Quantitative data were analysed using descriptive statistics, chi-square and ordinal regression tests while qualitative data were content analysed. The age of the students was 34.5±9.6 years, 57.8% were females, 26.8% were married, and 62.2% were employed. Learning increased with higher internet accessibility (x^2=64.8;df=1<0.05). Higher knowledge of internet informed better capability (x^2=55.6; df=1;p<0.05). Internet usefulness, and ease of use jointly explained 37.8% of variance in internet usage (Ϝ=0.869)=25.60;R^2=0.48; p<0.001). The NOUN learners indicated higher level of internet skill (R^2=2.48) than those from UI (R^2=2.18) and UNILAG (R^2=2.15). Students indicated that internet bridged communications and blurred boundaries but encouraged a strong move towards individualization and significantly affected interactions and interface between academics and learners. Number of male academics (60.5%) was almost twice the number of female (39.5%) academics. Internet-mediated teaching improved professional practice 53.4%, (UI), 46.2% (NOUN), 43.6% (UNILAG); support research 66.0% (UI), 53.0% (NOUN), 31% (UNILAG) and preparation of teaching materials 30.3% (UI), 28.3% (NOUN), 53.8% (UNILAG). Limitation to the use of internet was, however, associated with deficient infrastructural facilities 43.1%, (UI), 59.4% (NOUN), 47.3% (UNILAG); and inadequate technical trainings 58.3%, (UI), 56.3% (NOUN), 47.1% (UNILAG). Distance learning-mediated by internet was perceived to be more effective for supporting knowledge acquisition, skills and competences. Administrators and policy makers strongly argued that internet-mediated learning was a priority. Result indicated that poor infrastructural facilities, resistance to change and inadequate manpower inhibit non-integration of internet. The use of internet in distance learning has enhanced learning delivery in the sampled universities. Its usage should be strongly encouraged.